TELAAH MAQASYID SYARI’AH DAN HAK REPRODUKSI WANITA TENTANG KEPUTUSAN MEMILIH CHILDFREE - Ramadi, Bagus; Yusem, Nawir; Khoiri, Nispul (Pusat Studi Gender dan Anak, 2024)
The purpose of this study is to examine sharia maqashid and women's reproductive rights in the childfree phenomenon. The decision to be childfree raises a negative stigma from society. Childfree as a view regarding the decision that a married coupe wil choose not to have children in their home life. This concerns women's reproductive rights. The type and method of research that the author uses is a library research model with a qualitative approach. The results showed that having offspring is not an obigation but a right that can be chosen or abandoned with ful consideration and a sense of responsibility. And women's reproductive rights to the childfree paradigm are basicaly the right to freedom in determining what is the choice in life. In terms of Isamic law, the absence of a sharih nash or expressy prohibiting the practice of 'az that substantialy has similarities with Childfree shows that the act of Childfree is not prohibited by Shari'a. While in the maqashid view, the action of Childfree can manifest in various aspects, the proposal of al-khamsah depends on the ilat (factors) that drive a person to make a decision as a folower of Childfree